Reading Job with St. Thomas Aquinas - Vijgen, Jörgen; Levering, Matthew; Roszak, Piotr (Thomistic ressourcement series, 2020)
"Contributors examine Thomas Aquinas's exegesis of the Book of Job in relation to his philosophy and theology"--